2017
DOI: 10.1038/srep44873
|View full text |Cite
|
Sign up to set email alerts
|

KUS121, a VCP modulator, attenuates ischemic retinal cell death via suppressing endoplasmic reticulum stress

Abstract: Ischemic neural damages cause several devastating diseases, including brain stroke and ischemic retinopathies, and endoplasmic reticulum (ER) stress has been proposed to be the underlying mechanism of the neuronal cell death of these conditions. We previously synthesized Kyoto University substances (KUSs) as modulators of valosin-containing protein (VCP); KUSs inhibit VCP ATPase activity and protect cells from different cell death-inducing insults. Here, we examined the efficacy of KUS121 in a rat model of ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Furthermore, KUS administration was able to inhibit in vivo retinal neuronal cell death and mitigate disease phenotypes in several mouse models of retinal diseases, e.g. retinitis pigmentosa, glaucoma, and ischemic retinal disease ( Hasegawa et al, 2016b , Hata et al, 2017 , Ikeda et al, 2014 , Nakano et al, 2016 ). On the other hand, our previous results indicated that activation of nuclear receptors, specifically ERRs, would lead to increased ATP production in the targeted cells or organs ( Kamei et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, KUS administration was able to inhibit in vivo retinal neuronal cell death and mitigate disease phenotypes in several mouse models of retinal diseases, e.g. retinitis pigmentosa, glaucoma, and ischemic retinal disease ( Hasegawa et al, 2016b , Hata et al, 2017 , Ikeda et al, 2014 , Nakano et al, 2016 ). On the other hand, our previous results indicated that activation of nuclear receptors, specifically ERRs, would lead to increased ATP production in the targeted cells or organs ( Kamei et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under various stress conditions in cultured cells, the chemicals (KUSs) were able to significantly maintain cellular ATP levels, and consequently suppress ER stress and cell death ( Ikeda et al, 2014 , Nakano et al, 2016 ). In addition, KUSs showed significant efficacies in preventing retinal neuronal cell death in in vivo mouse models of retinitis pigmentosa, glaucoma, and ischemic retinal disease ( Hasegawa et al, 2016b , Hata et al, 2017 , Ikeda et al, 2014 , Nakano et al, 2016 ). In this manuscript, we show that two classes of small chemicals, one for limiting ATP consumption, and the other for enhancing ATP production via ERRs, possess strong efficacies in maintaining ATP levels and in protecting neuronal cells from death in both in vitro cell culture and in vivo mouse models of Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, KUS121 has been shown to be one of the most potent neuroprotective KUSs and has not shown any obvious safety issues in these animal experiments. Additionally, in rats with ischemic retinal injuries, either systemic or intravitreal administration of KUS121 suppressed death of the retinal ganglion cells, as well as subsequent deterioration of visual functions [19].…”
Section: Introductionmentioning
confidence: 93%
“…KUSs have been shown to maintain cellular ATP levels, function as intracellular ATP regulators, and consequently suppress ER stress and cell death under various cell death-inducing insults, both in vitro and in several pathological conditions in vivo [15,[17][18][19][20]. We have shown that KUSs can mitigate retinal pathologies in animal models of retinitis pigmentosa [15,17], glaucoma [18], age-related macular degeneration [20], and retinal ischemia [19]. Furthermore, KUS121 has been shown to be one of the most potent neuroprotective KUSs and has not shown any obvious safety issues in these animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…KUSs prevented ATP depletion, endoplasmic reticulum (ER) stress, and consequently cell death in cultured cells. KUSs consistently suppressed retinal neuronal cell death in animal models of ocular diseases, such as retinitis pigmentosa 15,16 , glaucoma 17 , and central retinal artery occlusion 18 .…”
mentioning
confidence: 96%